The Glimpse Traveler - Boruch, Marianne, 1950- (Book collections on Project MUSE., 2011)
When she joins a pair of hitchhikers on a trip to California, a young Midwestern woman embarks on a journey about memory and knowledge, beauty and realization. This true story, set in 1971, recounts a fateful, nine-day trip into the American counterculture that begins on a whim and quickly becomes a mission to unravel a tragic mystery. The narrator's path leads her to Berkeley, San Francisco, Mill Valley, Big Sur, and finally to an abandoned resort motel, now become a down-on-its-luck commune in the desert of southern Colorado. Neither a memoir about private misery, nor a shocking expos ̌of life in a turbulent era, The Glimpse Traveler describes with wry humor and deep feeling what it was like to witness a peculiar and impossibly rich time.